Risk Planning Analysis in Business Continuity Management of Container Villa Rental Companies - Awang Awang; Tanti Yanuar Rahmad; Rhian Indradewa; Muhammad Dhafi Iskandar (Syntax Corporation Indonesia, 2023)
In the villa container rental industry, risk is an integral part of business operations. Container villa rental companies need to ensure smooth and sustainable business continuity in the face of risks that may arise. The purpose of this study was to identify relevant risks in the business of a villa container rental company. This research uses a qualitative approach with a case study approach. Data will be collected through interviews with relevant parties in the villa container rental company, such as managers, employees, and other stakeholders. In addition, data will also be collected from documents related to risk management and business continuity. The collected data will be analyzed qualitatively using a thematic analysis approach. The results show that the rental of container villas in the mountains in Indonesia involves risks arising from uncertainties, such as variations in sales, operating costs, and operating leverage. Financial management can reduce risk by stabilizing these factors. In the container villa rental industry, risks include price, operational, and environmental competition, thus the need for risk management to identify and mitigate potential impacts.